Karakteristik pasien kebidanan dengan infeksi COVID-19 di Ruang Praja RSUD Wangaya Bali periode Mei - Desember 2020 - Johan Qalaba; Gede Alit Wardana (DiscoverSys Inc., 2021)
Background: Coronavirus disease 2019 (COVID-19) is a highly contagious disease caused by the SARS-COV2 virus. Pregnant women are important because pregnant women are more susceptible to viral infections and severe pneumonia due to physiological changes in the immune and cardiopulmonary systems during pregnancy, with manifestations ranging from asymptomatic to very severe. At this time, no research has been conducted on the local population, so that the authors will examine the characteristics of obstetric patients with COVID-19 infection in the Praja room of RSUD WANGAYA Bali. To determine the characteristics of midwifery patients with COVID-19 infection in the Praja room at Wangaya Bali Hospital for the period May 2020 - December 2020.Methods: This study was a retrospective descriptive study using medical records from mothers related to COVID-19. The inclusion criteria were obstetric patients with COVID-19 infection in the Praja room with the results of a reactive Rapid Test or RT-PCR at Wangaya Hospital. The data collected were age, parity, screening rapid test, comorbid, probable case, clinical symptoms, laboratory results, chest x-ray, baby weight and APGAR score, type of delivery, amount of postpartum hemorrhage, confirm case with RT-PCR, length of treatment, the need for ICU rooms and the number of deaths.Results: In this study, there were 67 respondents. Most of them were in the age range of 21-30 years and had given birth more than once. More than half of the respondents had a cesarean section, and most of the respondents tested positive for COVID-19 through the RT-PCR test. APGAR scores and baby weight were mostly normal. There were 62 respondents confirmed as RT-PCR, while with the Rapid reactive results, 66 people. Patients with mild anemia were found and found an increase in the number of CRP and neutrophils. Asymptomatic and non-comorbid patients were the most common, and on the x-ray image, most had pneumonia. There was no postpartum hemorrhage in either method of delivery. Only one person needs an ICU room. Patients infected with COVID-19 require a longer treatment time.Conclusion: Most were found in no comorbid and asymptomatic. Laboratory results were mostly found with mild anemia, leukocytosis with neutrophilia and high NLR, and high CRP. Most pregnant women do not need ICU care. Latar belakang: Penyakit corona virus 2019 (COVID-19) merupakan penyakit yang sangat menular yang disebabkan oleh virus SARS-COV2. Wanita hamil penting untuk diperhatikan karena wanita hamil lebih rentan terhadap infeksi virus dan pneumonia parah akibat adanya perubahan fisiologis pada sistem imun dan cardiopulmonal selama kehamilan, dengan manisfestasi dari tanpa gejala hingga sangat berat. Pada saat ini belum ada penelitian yang di lakukan pada populasi lokal, sehingga penulis akan meneliti karakteristik pasien kebidanan dengan infeksi COVID-19 di ruang Praja RSUD WANGAYA Bali. Untuk mengetahui karakteristik pasien kebidanan dengan infeksi COVID-19 di ruang Praja RSUD Wangaya Bali periode Mei 2020 - Desember 2020.Metode: Penelitian deskriptif retrospektif dengan data catatan medik dari ibu terkait COVID-19. Kriteria inklusi merupakan pasien kebidanan dengan infeksi COVID-19 di ruang Praja dengan hasil Rapid Test atau RT-PCR reaktif di RSUD Wangaya. Data yang dikumpulkan adalah usia, paritas, skrining rapid test, komorbid, probable case, gejala klinis, hasil laboratorium, ronsen thorax, berat badan dan skor APGAR bayi, jenis persalinan, jumlah perdarahan post partum, confirm case dengan RT-PCR, lama perawatan, kebutuhan ruang rawat ICU dan jumlah yang meninggal.Hasil: Pada penelitian ini terdapat 67 responden, sebagian besar berada dalam rentang usia 21-30 tahun dan sudah pernah melahirkan lebih dari satu kali. Lebih dari separuh responden jenis persalinannya merupakan seksio sesaria, dan sebagian besar responden positif COVID-19 melalui tes RT-PCR. Skor APGAR dan berat badan bayi sebagian besar normal. Terdapat 62 responden terkonfirmasi RT-PCR, sedangkan dengan hasil Rapid reaktif, sebanyak 66 orang. Ditemukan pasien dengan keadaan anemia ringan, serta di dapatkan adanya peningkatan jumlah CRP dan Neutrofil. Pasien tanpa gejala dan tanpa komorbid paling banyak dijumpai dan pada gambaran ronsen terbanyak mengalami pneumonia. Tidak terdapatnya perdarahan post partum pada kedua metode persalinan. Hanya 1 orang yang memerlukan ruangan ICU. Pasien terinfeksi COVID-19 memerlukan waktu perawatan yang lebih lama.Kesimpulan: Sebagian besar ditemukan dalam tanpa kmorbid dan tanpa gejala. Hasil laboratorium sebagian besar ditemukan dengan anemia ringan, leukositosis dengan neutrofilia dan NLR tinggi, serta CRP tinggi. Sebagian besar ibu hamil tidak mebutuhkan perawatan ICU.